A Critical Review on Netra Tarpana: Netra Kriyakalpa Procedure - Smriti Kaul; Narender Chanchal (International Journal of Ayurveda and Pharma Research, 2025)
Netra (eye) is an important sense organ. Netra Tarpana is a classical Ayurvedic ocular therapy used for the nourishment and rejuvenation of the eyes. This procedure involves retaining medicated ghee over the eyes within a well formed by a dough ring, allowing the medicament to bathe the ocular structures for a specified duration. Rooted in the principles of Rasayana and Chakshushya therapy, Netra Tarpana is especially indicated in conditions caused by Vata and Pitta dosha imbalances, such as dry eyes, eye strain, computer vision syndrome, and degeneration of ocular tissues. The therapy enhances visual acuity, reduces fatigue, and promotes overall ocular health. The holistic and non-invasive nature of Netra Tarpana makes it a valuable addition to contemporary ophthalmic care, especially for preventive and promotive eye health. In this article, the procedure, mode of action, indications, contraindications, formulations, and the therapeutic outcomes observed in clinical practice are described.